Strenghtening Reversed Authentication for the Money Laundering Act with the Predicate Offense of Corruption in an Effort to Return the State Financial Losses - ., Hartiwiningsih (2016)
This dissertation research aims to determine, assess, and analyze the causes of the difficulty of implementation of the system of reversed authentication in the eradication of money laundering with corruption cases substantially, from the aspect of legal system. This study is also prescriptive; to create an optimal model for reversed authentication system in money laundering. This formulation is expected to be a breakthrough in the framework of the law indemnification of state financial. This study is a non-doctrinal legal research. The research approach is the approach of legislation, a comparative approach, and case approach. The data used are primary data and secondary data. Various obstacles encountered in the implementation of this reversed authentication system. Obscurity system settings of reversed authentication, the principle of disobedience and lawlessness events in AML Law, causes ineffective, bias and lead to contradictions in its application. On the other hand, the institutional structure of law enforcement officers do not apply synergistic, particularly in activities exposing the predicate crime, namely corruption, and weak asset tracing, the impact is the lack of indemnification of state. Judicial practice so far, does not give priority to the predicate crime, the charges of money laundering separated from the underlying predicate crime. Asset tracing is also not maximizing in collecting the evidence related to the predicate crime. Legal culture factor also does not yet support the operation of the law enforcement system, due to the low awareness and honesty of society, including law enforcement officers. Related to the constraints encountered, it is submitted recommendations, such as: the approach needs to be formulated in rem and illicit enrichment in the Law on Money Laundering and the Law on Corruption Eradication. It is extremely beneficial for the process of reversed authentication. In addition, there should be a procedural law governing the procedures, mechanisms and legal consequences in application of reversed authentication, both for the defendant and the public prosecutor. On the institutional aspects of law enforcement, asset tracing function should be empowered with the support of an investigative audit. The existence of clear standards in the coordination and supervision functions performed by the Corruption Eradication Commission (KPK) in the form of uniformity in eradicating money laundering and corruption must be absolutely exist. In terms of strengthening the legal culture against law enforcement officers carried out by applying the function of reward and punishment. As for the public, the socialization and education efforts are continuous and efficient by involving all the relevant elements. Keywords: strenghtening system, reversed authentication, money laundering, return the state financial losses.